Chromosome abnormalities in embryos derived from microsurgical epididymal sperm aspiration and testicular sperm extraction - Shao-Ping Fred Weng; Mark W. Surrey; Hal C. Danzer; David L. Hill; Pau-Chung Chen; Tsung-Chieh Jackson Wu (Elsevier, 2014)
Objective: To evaluate the patterns of chromosome abnormalities in embryos derived from intracytoplasmic sperm injection (ICSI) in microsurgical epididymal sperm aspiration (MESA) or testicular sperm extraction (TESE) in comparison to embryos that are derived from naturally ejaculated (EJAC) patients. Materials and methods: Male partners with azoospermia who required MESA or TESE for ICSI were studied for chromosomal abnormalities. The ICSI patients with EJAC sperm served as the control group. Preimplantation genetic diagnosis (PGD) was performed by fluorescence in situ hybridization (FISH). Chromosome abnormalities were categorized as polyploidy, haploidy, aneuploidy, and complex abnormality (which involves more than two chromosomes). Fertilization, embryo development, and patterns of chromosome abnormalities were accessed and evaluated. Results: There was no difference between the MESA, TESE, and EJAC patient groups in the rates of fertilization and pregnancy and the percentages of euploid embryos. In all three groups, less than one-half of the embryos for each group were normal (41 ± 31%, 48 ± 38%, and 48 ± 31% in MESA, TESA, and EJAC, respectively). Complex chromosomal abnormality was significantly more frequent in the MESA group than in the EJAC group (48.3% vs. 26.5%, respectively; p < 0.001). Furthermore, the overall pattern of chromosomal aneuploidy was similar among all three studied groups. Conclusion: We suggest that MESA and TESE, followed by ICSI and PGD, appear to be acceptable approaches for treating men with severe spermatogenesis impairment.